Does the market value value-added? Evidence from housing prices after a public release of school and teacher value-added - Scott Andrew Imberman; Michael Lovenheim (Center for Economic Studies and ifo Institute (CESifo), 2013)
Value-added data are an increasingly common evaluation tool for schools and teachers. Many school districts have adopted these methods and released the results publicly. In this paper, we study the release of value-added data in Los Angeles by the Los Angeles Times newspaper to identify how measured value-added is capitalized into housing prices. This analysis is the first in the school valuation literature to examine property value responses to a value-added information shock, which is of interest as this measure is less correlated with demographics than typical school quality measures. Unique to this setting as well is the release of both school and teacher-level value-added data, which allows us to examine how property values respond to both types of information. Using a difference-indifferences methodology surrounding the release, we find that neither school nor teacher value-added scores are capitalized into home prices. Our results suggest that, despite the contentiousness following these data releases, homeowners do not consider value-added models as currently constructed to be a relevant school quality measure on the margin.
Keywords: H41; I20; R30; 330; value-added; housing prices; capitalization; school quality; Schule; Dienstleistungsqualität; Bewertung; Mediale Berichterstattung; Immobilienpreis; Los Angeles (Calif.)